The Role Of Islamic Financial Technology In Achieving Financial Inclusion - Belgourari Hadjer; Salah Hichem (جامعة الوادي University of Eloued, 2024)
This study aims to clarify the role of Islamic financial technology in achieving financial inclusion, as financial technology has revolutionized financial services and established effective solutions to target people deprived of various financial services; in addition to understanding how Islamic financial technology can achieve financial inclusion, by relying on the descriptive approach to defining the concepts of financial technology and Islamic financial technology, while simplifying the most important financial technology techniques, as well as the analytical approach to monitor the development of financial inclusion and Islamic financial technology globally. The study concluded that Islamic financial technology is growing and expanding significantly as an indispensable economic necessity. However, the field of using Islamic financial technology still needs to overcome many challenges that hinder its expansion globally.
Keywords: Financial technology; Islamic Fintech; financial inclusion; financial industry